2013
DOI: 10.4103/0970-9290.116688
|View full text |Cite
|
Sign up to set email alerts
|

A 10-year retrospective study on odontogenic tumors in Iran

Abstract: Although there are few studies on odontogenic tumors in literature, the comparison of our results with existing data shows significant differences in the distribution of tumors and age of patients, which may be due to ethnic features and geographic distribution of patients. Future studies on other ethnic groups are essential for further clarification of the findings in this research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
15
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 26 publications
13
15
1
3
Order By: Relevance
“…The data are in agreement with the rate of studies that showed a relative frequency of OM in Asia, Europe, and America varying between 0.5% and 17.7% . In addition, the studies analyzed in the present review demonstrated a relative incidence of OM of 4.5% in Africa, 8.8% in America, and 10.64% in Asia, demonstrating a geographic variation in the prevalence of OM. The comparison of the real prevalence of this lesion in different regions may be difficult mainly because of the different periods of analysis in each population and the relative lack of epidemiological studies about OM .…”
Section: Discussionsupporting
confidence: 91%
“…The data are in agreement with the rate of studies that showed a relative frequency of OM in Asia, Europe, and America varying between 0.5% and 17.7% . In addition, the studies analyzed in the present review demonstrated a relative incidence of OM of 4.5% in Africa, 8.8% in America, and 10.64% in Asia, demonstrating a geographic variation in the prevalence of OM. The comparison of the real prevalence of this lesion in different regions may be difficult mainly because of the different periods of analysis in each population and the relative lack of epidemiological studies about OM .…”
Section: Discussionsupporting
confidence: 91%
“…The very high frequency of occurrence for benign OTs was again reaffirmed by the results of this study where benign tumours constituted about 98.3% of all the OTs observed in this series. Ameloblastoma, a benign but locally aggressive slow-growing OT (7), was the most frequently observed tumour, and this is consistent with earlier reports from Nigeria and other parts of Africa and Asia (2,8,13). This contrasts with reports from the Western world that found odontomas as the most frequently observed OT (10,11,14).…”
Section: Discussionsupporting
confidence: 85%
“…Odontogenic tumours (OTs) are derived from epithelial and mesenchymal elements that are part of the toothforming apparatus (1,2) and must be considered as a differential diagnosis when analysing jaw lesions (3). They may be cystic, myxomatous or sometimes have a mixture of cystic and solid areas.…”
Section: Introductionmentioning
confidence: 99%
“…[1] In contrast to ameloblastoma which is well documented, little is known about AC. To date, 92 cases of AC have been presented in the literature showing its rarity.…”
Section: Introductionmentioning
confidence: 99%